A Comparative Study of Stakeholder Engagement in the Dual Education System: A Case of Germany, the United States and Kazakhstan - Artykbayeva, Aizhan; Greiman, Virginia A. (Journal of Technical Education and Training, 2023)
Stakeholder engagement in the dual education system is one of the key factors in developing a sustainable educational system. In this study, the authors aim to explore the role and responsibilities of the key stakeholders and the level of their engagement in the dual education system. The authors aim to contribute to stakeholder engagement in dual education by identifying, assessing, and prioritizing project stakeholders’ interests and influence on the education system. The paper used a case study approach and conducted semi-structured interviews with representatives of vocational schools in Kazakhstan. The case study was conducted by comparing the results of the project stakeholder analysis in the dual education systems of Germany and the United States to Kazakhstan. The semi-structured interviews were conducted with 15 experienced educators from different vocational schools in Kazakhstan. The author’s analysis reveals that significant changes are necessary to the legislation in Kazakhstan to improve the dual education system.